Is Bigger Better? Living Donor Kidney Volume as Measured by the Donor CT Angiogram in Predicting Donor and Recipient eGFR after Living Donor Kidney Transplantation. (10th July 2021) - Ebad, Chaudhry Adeel; Brennan, David; Chevarria, Julio; Hussein, Mohammad Bin; Sexton, Donal; Mulholland, Douglas; Doyle, Ciaran; O'Kelly, Patrick; Williams, Yvonne; Dunne, Ruth; O'Seaghdha, Conall; Little, Dilly; et al.
Abstract : Background . The role of kidney volume measurement in predicting the donor and recipient kidney function is not clear. Methods . We measured kidney volume bilaterally in living kidney donors using CT angiography and assessed the association with the donor remaining kidney and recipient kidney (donated kidney) function at 1 year after kidney transplantation. Donor volume was categorized into tertiles based on lowest, middle, and highest volume. Results . There were 166 living donor and recipient pairs. The mean donor age was 44.8 years (SD ± 10.8), and donor mean BMI was 25.5 (SD ± 2.9). The recipients of living donor kidneys were 64% male and had a mean age of 43.5 years (SD ± 13.3). Six percent of patients experienced an episode of cellular rejection and were maintained on dialysis for a mean of 18 months (13–32) prior to transplant. Kidney volume was divided into tertiles based on lowest, middle, and highest volume. Kidney volume median (range) in tertiles 1, 2, and 3 was 124 (89–135 ml), 155 (136–164 ml), and 184 (165–240 ml) with donor eGFR ml/min (adjusted for body surface area expressed as ml/min/1.73 m 2 ) at the time of donation in each tertile, 109 (93–129), 110 (92–132), and 101 ml/min (84–117). The median (IQR) eGFR in tertiles 1 to 3 in kidney recipients at 1 year after donation was 54 (44–67), 62 (50–75), and 63 ml/min (58–79), respectively. The median (IQR) eGFR in tertiles 1 to 3 in the remaining kidney of donors at 1 year after donation was 59 (53–66), 65 (57–72), and 65 ml/min (56–73), respectively. Conclusion . Bigger kidney volume was associated with better eGFR at 1 year after transplant in the recipient and marginally in the donor remaining kidney.